Manajemen Perubahaan Pada UMKM Pasca Pandemi Covid-19 Dengan Memanfaatkan Teknologi Informasi - Diah Safri Yulinda; Nuri Aslami (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study uses qualitative methods, how the data is taken from the internet media that is quite credible, books and scientific journals. For my own data analysis technique, I use interpretation, narrative and content analysis. During the Covid-19 pandemic, many MSMEs experienced a decline in income, even to the point of closing their companies. To survive in the Covid-19 pandemic, change management is needed by utilizing internet information. Because today’s information technology is increasingly advanced, we can see many things easily and information technology functions as an information processor available at this time. Change management provides a structure to assist individuals in an organization to transition or change from their current state to their desired state. Organizational change management is concerned with identifying the groups and individuals who must change. Not only that, organizational change management requires the development of appropriate plans to successfully implement changes